مصادر الأحكام الفقهية المتفق عليها - عثمان، فيروز عثمان صالح (جامعة الخرطوم - كلية الاداب - قسم الدراسات الإسلامية, 2009)
This study discusses an important issue which is the Figh rules agreed on try the Muslim scientists. These are the Holy Qura'an, Sunna, Collectiveness, and Measurement. The study provides a definition for the divisions of these rules and their types. It also introduces the Holy Qura'an and illustrates its rules types as well as their use as evidences. \ The study shows the parts of Sunna, its evidence on rules. In addition, it defines the collectiveness and measurement, shows their pillars and prooveness mentioning some prooves.
تتناول هذه الدراسة موضوعاً مهماً وهو "مصادر الأحكام الفقهية المتفق عليها عند جمهور علماء المسلمين"، وهي القرآن والسنة والإجماع والقياس. \ وستبين الدراسة التعريف بأقسام الأحكام وأنواعها، وكذلك التعريف بالقرآن الكريم، وبيان أنواع أحكامه، وكذلك حجية أحكامه، والسنة النبوية وبيان أقسامها ودلالتها على الأحكام. \ وكذلك التعريف بالإجماع والقياس وبيان أركانهما وحجيتها والأدلة على ذلك.
Keywords: الأحكام الفقهية -- الأدلة الشرعية -- المصادر الشرعية